The ever-evolving landscape in sports communication: gaining insights from collegiate athletics - Meier, Anthony Alexander (Kansas State University, 2015)
Communication in sports continues to rapidly evolve, redefining roles of not only the fan, but the traditional media and the organization’s sports public relations professionals as well. The latter in particular has seen their role grow tremendously as new media continues to break down barriers between fan and organizations, giving them considerable influence on the slew of new content available to fans as well as how traditional media will cover sports in general. Utilizing Bey-Ling Sha’s Dimensions of Public Relations, this study employs in-depth interviews with the top communications professionals in the Big 12 to gain further perspective on the roles played by the fans and traditional media in the communication process, while also further gaining insight into the sports PR field.
Keywords: Sport; Traditional; New media; Dimensions of Public RelationsCommunication; Communication (0459); Mass Communications (0708); Sports Management (0430)